Moisture sorption isotherm and thermal characteristics of freeze-dried tuna - Mohammad Shafiur Rahman; Mohammed Khalfan Al-Khusaibi; Kutaila Abbas AL-Farsi; Ismail Mohamed Al-Bulushi; Aisha Abushelaibi; Nasser Al-Habsi (International Journal of Food Studies)
Water activity is considered an important factor in assessing the stability of food. Understanding the relationship between water activity and equilibrium moisture content (moisture sorption isotherm) benefits food processing in terms of modeling of drying and estimation of shelf life. In addition, glass transition helps to quantify molecular mobility which helps in determining the stability of food. The aim of this study was to determine the moisture sorption isotherm and thermal characteristics of freezedried tuna. These characteristics will help in determining the monolayer moisture and glassy state of the product, at which food is considered most stable. Moisture sorption isotherm at 20 oC and thermal characteristics (over a wide temperature range i.e. from -90 to 250 oC) of freeze-dried tuna flesh were measured. Isotherm data were modeled by BET (Brunauer-Emmett-Teller) and GAB (GuggenheimAnderson–De Boer) models. The GAB and BET monolayer water values were determined as 0.052 and 0.089 g g−1 dry-solids (dry-basis), respectively. In the case of samples at moisture contents above 0.10 g g−1 (wet basis), DSC (Differential Scanning Calorimetry) thermograms showed two-step state changes (i.e. two glass transitions), one exothermic peak (i.e. molecular ordering) and another endothermic peak (i.e. solids-melting). However, the sample at moisture content of 0.046 g g−1 showed three-step state changes (i.e. three glass transitions). The multiple glass transition could be explained by the natural heterogeneity of tuna flesh and inhomogeneity due to molecular incompatibility of the different compositions. The moisture content did not affect the first glass transition temperature nor the exothermic peak (p>0.05), whereas the third glass transition temperature decreased (i.e. plasticized) with increasing moisture content (p<0.05). The solids-melting peak temperature decreased, and enthalpy increased with decreasing moisture content (p<0.05).